Beyond Screen Time: Parenting Styles, Psychological Well-Being, and Online Game Addiction among Indonesian Adolescents and Young Adults - Rendy Alfiannoor Achmad; Katamsi Tri Pratiwi Julia Elvananta; Taruli Artha Butar Butar; Muhammad Abdan Shadiqi (Utan Kayu Publishing, 2026)
Online game addiction has become an important issue among young people in Indonesia, particularly within a cultural context where parenting remains highly influential in shaping psychological development. This study examined the relationship between parenting styles, psychological well-being, and online game addiction among individuals aged 15–30 years. It was hypothesized that parenting styles would be associated with online game addiction both directly and indirectly through psychological well-being. A quantitative cross-sectional design was used, involving 601 participants recruited through digital outreach on Instagram, Twitter, and Facebook with 519 final respondents. Data were collected using the Indonesian Online Game Addiction Questionnaire, the Parental Authority Questionnaire (PAQ), and Triwahyuni and Prasetio’s 42-item Psychological Well-Being Scale. The findings showed that paternal and maternal parenting styles were negatively associated with psychological well-being. Psychological well-being also mediated the relationship between parenting styles and online game addiction, indicating that parenting may influence gaming behavior through its impact on psychological functioning. These results highlight the importance of considering both family dynamics and psychological well-being in understanding online game addiction among Indonesian young people.